Politainment as a Speech Event: A Socio-Pragmatic Analysis of Participation in Political Satire Shows - Ismail, Shawqi; Al Ubaidy, Sundus (Al-Adab Journal, 2025)
This study is an attempt to approach the notion of politainment from the socio-pragmatic framework of participation. Politainment is a relatively new concept that describes a merge between the political and entertainment genres as a result of the effect of modern media platforms on politics. It falls into two main categories: political entertainment, and entertaining politics. Political entertainment usually involves the utilisation of political agendas in entertainment like movies and music; while entertaining politics involves the politicians attending entertainment events to advocate for their political agendas. The focus of the current study is on entertaining politics as a speech event. The event in question is a political satire show. This study tries to analyse such event in terms of the socio-pragmatic notion of participation which tries to account for the different production and reception roles played by the politician and the other people in these shows in order to establish the speech event itself. The sample of the study consists of an interview with a politician in an entertainment show. The main finding of this study is that this type of events tends to be more on the entertainment side than adopting a political theme.